ANALYSIS OF SUSTAINABLE PROPERTY BUSINESS DEVELOPMENT STRATEGY IN NORTH SUMATRA REGION AT PT. XYZ - Muhammad Habib Rizki; Tuti Sarma Sinaga; Nazaruddin (CV. Radja Publika, 2026)
This study aims to analyse the sustainable property business development strategy implemented by PT XYZ in North Sumatra, identify supporting and inhibiting factors, and formulate strategic recommendations to enhance the company's competitiveness. This research adopts a qualitative approach, using a case study and SWOT analysis as the main analytical frameworks. Data were collected through direct observation, in-depth interviews with company management, and analysis of PT XYZ's internal documents and Ministry of Public Works and Housing (PUPR) data on FLPP quotas for the period 2021–2025. The results indicate that PT XYZ's KPR Subsidi/FLPP sales performance fluctuated during the study period, with annual sales realisations ranging from 55 to 142 units and an average FLPP quota absorption rate of 0.70%. Five recommended sustainable business development strategies include: comprehensive long-term planning, strong positioning as a trusted local developer, integrated digital marketing, effective human resource management, and product and service differentiation oriented toward sustainability. The main supporting factors include North Sumatra's population growth, Medan's geographical advantages, and regional economic growth. The main inhibiting factors are competition from national developers, low consumer literacy, volatility in building material prices, and credit default risk. Concludes that optimal utilisation of the KPR Subsidy/FLPP program through an integrated strategy will increase the company's business capacity and social contribution in providing decent housing for low-income communities in North Sumatra.